Fobia social e incidencia en el rendimiento académico de paciente femenino de 15 años - Mendoza Sierra, Nathaly Elizabeth (2019)
This case study, it is a teenager with difficulties, family, emotional, educational for this work social area were applied by the techniques used for data collection, such as semi-structured interview, clinical observation, medical history and psychometric testing, it was determined the signs and symptoms manifested disproportionate teen to situations or social events, cultures, family and how they affect academic performance. Through the syndromic picture and the Diagnostic and Statistical Manual of Mental Disorders, could be identified that the teenager had a 300.23 (. F40 10) Social anxiety disorder (social phobia), so we proceeded to apply appropriate treatment, further suggesting that seminars, workshops, dialogues are developed; among other activities where we provide more information on the subject both teachers and parents for the prevention and detection of the disorder.